Correction: Interfacial modification between argyrodite-type solid-state electrolytes and Li metal anodes using LiPON interlayers. Issue 2 (26th January 2023) - Su, Jin; Pasta, Mauro; Ning, Ziyang; Gao, Xiangwen; Bruce, Peter G.; Grovenor, Chris R. M.
Abstract : Correction for 'Interfacial modification between argyrodite-type solid-state electrolytes and Li metal anodes using LiPON interlayers' by Jin Su et al., Energy Environ. Sci., 2022, 15, 3805–3814, ; https://doi.org/10.1039/D2EE01390H .